Olusegun Obasanjo : the presidential legacy, 1999-2007 - Akinkugbe, O. O. (Ibadan, Nigeria : Bookcraft, 2013)
The essays aim to capture the major highlights of Obasanjo's two-term tenure 1999-2007. They cover Infrastructure; The Social Services- Education, Health, Science and Technology; Social and Food Security; Ethical Challenges and the Crisis of Transparency; Oil, Finance & the Economy; International Affairs; Power in Megawatts; Power and its Separation in Legal Tongue.
Includes bibliographical references and index.
ije 28/06/2017
Loans
Keywords: Obasanjo, Olusegun; Heads of state; Generals; Presidents; Politics and government; Nigeria. Nigerian Army; Nigeria